MODEL COOPERATIVE LEARNING TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA KELAS V SEKOLAH DASAR - Atika Dwi Evitasari; Wiwin Setyani (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
This study aimed to see the improvement of students’ learning outcomes through the application of the jigsaw cooperative learning model in science subjects for the 5th grade students in elementary schools. The research method used classroom action research which consisted of three stages in each cycle which included: 1) planning, 2) implementation and observation, and 3) reflection. The research subjects were 20 students. The research data collecting techniques were the test and observation sheet. Data analysis used qualitative and quantitative descriptive analysis techniques. The results showed that the application of the cooperative learning model withjigsaw type could improve students’ learning outcomes in science subjects for the 5th grade students in elementary schools. This result was proven by the increase in learning outcomes of students in science subjects, in the first cycle the value of students was 64.25 and 9 children (45%) had reached the Minimum Completeness Criteria (KKM). In the second cycle, there was an increase in learning outcomes with a value of 88.00 and 18 children (90%) had reached the Minimum Completeness Criteria (KKM).